Docência com bebês: experiências sociais e dimensão sensorial no trabalho de professoras e auxiliar no cuidado e educação de bebês em uma Instituição de Educação Infantil - Laís Caroline Andrade Bitencourt (2020)
This article aims to understand the teachers and their assistants’ experiences in children’s education, who take care and educate babies at a full-time public institution in Belo Horizonte. The literature review evidenced the ongoing construction of the character of the early childhood education institution and the teaching identity of these teachers and their assistants. It was highlighted in those studies that teaching babies has some specific characteristics and requires the mastery of theoretical, methodological and interpersonal skills, intertwined with subtle actions. The proficiency of knowledge and practice collected from the experiences of several generations of women is present in the relationships between teachers, assistants, and children, during the performance of caring and educational activities, which were neither acquired in courses nor have any institutional recognition. These professionals gather values, feelings, and logic that involve actions, which influence both the intellectual and emotional dimensions of human experience, which are intertwined with health and education when interacting with babies. This research is focused on this scenario. The theoretical perspectives adopted were “The Sociology of Experience” developed by François Dubet, “The Care Work”, which is a concept of caring as a category of the sociology of work, and at last “The anthropology of senses” developed by David Le Breton. It regards a qualitative approach investigation with an empiric base. The instruments used were: a) participant observation with a daily field report, b) film shootings, and c) semi-structured interviews. The data was collected between march and December 2017 at a municipal public institution of children’s education in Belo Horizonte by the observation of two baby classes placed in the same space. The research was done with nine teachers and an assistant. The analyses provided reflections on the teachers and assistant’s experience while working with babies at this school. They evidenced the connection between teaching and technical, affective, emotional and sensorial aspects. Teachers and assistants develop different logic of action while performing their work activities, which directly affects the baby’s experience. As an original contribution, given the confirmation of the researches on the use of one’s own body as a work tool for teachers and assistants, it is offered an approach for an intertwined dimension between the logic of action and the sensorial dimension present in the performance of teaching and caring. This sensorial dimension allows a better understanding of subtle actions in the performance of teaching and caring. An analysis that evidences the hearing of the color of caring these women perform, in a collective environment, with beings who cannot perform self-care independently with their bodies. It is a dimension that draws attention to the fact that the constitution of the social experience of teachers and assistants goes beyond, besides the logic of integration, strategy, and subjectification, the first senses of the body in the established daily routines.